PENGARUH PENGGUNAAN APLIKASI SPARCOL VIDEOSCRIBE TERHADAP KEMAMPUAN MENYIMAK SISWA - Bustamin Lamalla; Muhammad Hanafi; Suleha Ecca (Program Studi Pendidikan Bahasa Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sidenreng Rappang, 2019)
The purpose of this study was to determine the effect of using the Sparcol videosribe application on the ability to listen to Grade VII students of SMP Negeri 1 Baranti, Sidenreng Rappang Regency. This research is a quasi-experimental study with a population of 57 people and using a total sample. The data in this study were collected through documentation and test techniques. Data were analyzed with descriptive statistical techniques namely mean. The results showed that the use of the Sparcol Videoscribe affected of listening ability of Grade VII students SMP Negeri 1 Baranti, Sidenreng Rappang Regency. This can be seen from the average value of the experimental group which is higher than the average value of the control group namely Mx = 83,44> My = 75. Therefore, it is concluded that there is an influence of the use of the Sparcol Videosribe application to the listening ability of Grade VII students SMP Negeri 1 Baranti, Sidenreng Rappang Regency, 2018/2019.